Cross domain innovations in Electric vehicles: management of Energy and Connectivity challenges - 1Dr. Radhika V; K. Euchristmary; K. Shreepranav (The Bioscan, 2025)
The quick growth of electric vehicle (EV) infrastructure has created severe problems regarding energy management and connection. The combination of smart grid advancements along with battery chemistry research and vehicle communication systems must happen because of these barriers. The research explores contemporary methods and approaches dedicated to enhancing EV energy consumption along with vehicle-to—everything (V2X) connectivity. Research analysis shows three key findings about car communication protocols as well as intelligent charging infrastructure and predictive energy control systems. This document presents descriptions of actual implementations together with substantial effect descriptions regarding green transport systems. A multimodal approach is necessary to manage the interactions between interconnected vehicle systems and energy distribution networks according to the study outcomes.